Impact of financial literacy on investment decisions in developing countries: The example of Kazakhstan - Bayakhmetova, Aliya; Bayakhmetova, Leyla; Bayakhmetova, Lyazzat (Asian Development Policy Review, 2023)
This study aims to establish the impact of financial literacy on investment decision-making in developing countries, with the Republic of Kazakhstan serving as a case study. The research approach involved conducting a questionnaire survey for Kazakhstan residents to evaluate their level of financial literacy, followed by analysis of the results through the SPSS software. To evaluate the influence of financial literacy on the efficiency of investment decision-making, a correlation analysis was performed on two variables: the financial literacy index and the investment decision-making efficiency index. The findings indicate that respondents' financial literacy level has an impact on investment decision-making. After all, a higher level of financial literacy indicates a larger number of individuals who have made financial investments at least once, while among respondents with a lower level of financial literacy, approximately 30% did not invest at all. The impact of financial literacy on effective investment decision-making is dependent on age, education, and financial criteria. Moreover, personal income plays a pivotal role in facilitating informed investing choices. The proposed study has practical applications for financial and credit institutions, banks, and government officials in establishing a basis for efficiently injecting finances into the economy of a developing nation.